Construcción de un vector de expresión cloroplástica para transformación genética de Ankistrodesmus sp. - Castro Cobos, Carlos Gilberto (2022)
Microalgae are suitable for use as biotechnological platforms for the elaboration of recombinant proteins. However, in order to take advantage of them, it is necessary to design appropriate expression vectors. In that sense, the chloroplast is an excellent organelle to produce recombinant proteins in a numerous and compartmentalized way. Therefore, the main aim of this research was to construct a chloroplast expression vector for Ankistrodesmus sp. To achieve this goal, bioinformatics tools were used from the assembled and annotated sequences of the chloroplast genome of the studied species. The transcriptional regulatory regions (promoters and terminators) in the atpA, psbA, psbC and rbcL genes, commonly used to design chloroplastic expression vectors, were identified in this genome. Likewise, based on the coding region of these genes, a codon frequency table was obtained, which was used to optimize sequences of the hph and ama-1 transgenes so that they could be incorporated into the vector and expressed in the chloroplast. Subsequently, using Gibson's assembly strategy, the chloroplastic expression vector pANK-v1 was constructed in silico. In conclusion, we were able to construct in silico a chloroplastic expression vector for Ankistrodesmus sp.